A new genus and a new species of Sphodrini (Coleoptera: Carabidae) from Changbai Mountain, China, with notes on the tribe - Zhu, Pingzhou; Shi, Hongliang; Liu, Shengdong; Liang, Hongbin (Zootaxa, 2024)
A new genus and a new species of the sphodrine subtribe Dolichina are described: Peiyuia changbaiensis Zhu & Shi, gen. nov., sp. nov. (type locality: China, Jilin, Changbai Mountain, 42.1077°N, 128.0957°E, altitude 1415 m). A key is provided for the eight known genera of Dolichina. Relationships of the genera of Dolichina and some characters of the subtribe are discussed. Two species of Sphodrini are newly reported from China: Morphodactyla coreica (Jedlička, 1937) and Pristosia latistoma Sasakawa, J.L. Kim, J.K. Kim & Kubota, 2006.